Inter-ethnic Partnerships: Key Characteristics, and What They Reveal about Successful Integration - Olga Nottmeyer (Weekly Report, 2010)
Partnerships between immigrants and native-born citizens are commonly viewed as the product of successful social integration, as well as a possible driving force of economic success. Thus, immigrants living in inter-ethnic partnerships have on average a higher level of education, better occupational status, and higher income than those living in intra-ethnic relationships. Data from the German Socio-Economic Panel Study (SOEP) show that immigrants in relationships with native Germans describe themselves on average as particularly communicative and open. However, in this area there is no difference between Germans in inter-ethnic relationships and those in German-German partnerships. Similarly, readiness to take risks and general life satisfaction are not above average among Germans in inter-ethnic relationships. By contrast, immigrants in inter-ethnic relationships evaluate themselves as particularly willing to take risks and interested in politics. In addition, they see themselves as less often subject to discrimination than immigrants living in intra-ethnic partnerships.
Keywords: J12; J15; J0; 330; Intermarriage; Big 5 Personality Traits; Migration